Perkembangan Bahasa, Moral, dan Psikososial: Suatu Kajian Teoretis - Siregar, Yahpuri Ayunda; Ramadani, Putri Amalia; Fitriani, Wahidah (Lembaga Yasin AlSys, 2026)
Language, moral, and psychosocial development during adolescence constitutes a critical phase in shaping character and identity, thereby requiring educational approaches that can integrate these three aspects to support adolescents in facing physical, cognitive, and social developmental challenges. This article aims to theoretically analyze the relationships among language, moral, and psychosocial development in adolescents and their implications for educational practice. The study employs a literature review method through stages of collecting, identifying, classifying, and critically analyzing relevant scholarly sources. The analytical process includes a review of the basic concepts of language, moral, and psychosocial development, as well as their interconnections in the context of adolescent development. The findings indicate that language functions not only as a medium of communication but also as a tool for moral reasoning that mediates the internalization of values and ethical decision-making, while psychosocial development is strongly influenced by social interactions and environmental factors, including family, school, and the wider community. The discussion underscores the need for integrative educational approaches so that the development of language, moral, and psychosocial aspects can proceed synergistically, enabling adolescents to grow into intellectually competent, morally grounded, and psychosocially healthy individuals who are capable of navigating social dynamics in the era of globalization. Accordingly, learning practices that combine the strengthening of language competence, the cultivation of moral values, and psychosocial support emerge as key strategies to promote holistic adolescent development.